Una experiencia que dejó huella (VITAL, 2025)
Jhordan Yesid Ramírez Rojas, a seventh-semester medical student, recounts his experience as a volunteer at the Euroweeken 2024 summer camp, which focused on improving the English skills of Polish and Turkish students. His journey began in July 2024, with his first exposure to Europe through Paris, Amsterdam, and Berlin, where he reaffirmed his interest in practicing medicine in Germany.In Poland, the volunteering experience allowed him to connect with young people from diverse nationalities, united by the English language. During his free days, he explored various cities in Poland and subsequently traveled through Slovenia, the Czech Republic, Austria, and Bulgaria with a companion. His return to Colombia, with a final stop in Paris, brought a mix of happiness for reuniting with family and nostalgia for the experiences and friendships he had forged. This adventure, which he considers transformative, left a significant mark on his life.